Kompetensi Strategis Siswa Tipe Melankolis dalam Menyelesaikan Masalah Matematika pada Kesebangunan - Laikha Sari; Tatag Yuli Eko Siswono; Manuharawati Manuharawati (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to describe the strategic competence of students in solving story problems in Congruence. This research uses descriptive qualitative research method with 15 students in class IX-A as the subject. The subject selection test used is a personality test of students who have a melancholic type which is adapted directly from the instrument that has been compiled by Florence Littauer. From the sampling of melancholic type students, strategic competencies will be analyzed in solving math problems on the similarity material. The results of personality tests for students in grades IX-A are 2 students who are melancholic type, 4 students are choleric type, 4 students are phlegmatic type, 5 students are sanguinis type. Two students, namely 2 males with a melancholic personality type, were selected as research subjects for a strategic competency test and continued with interviews based on strategic competency indicators. The results of data analysis showed that 2 students met the indicators of strategic competence in solving mathematical problems in the Comparison material. Melancholy type students fulfill strategic competence indicators, namely understanding the situation and conditions of a problem, finding key words and ignoring irrelevant things from a problem, presenting problems mathematically in various forms, choosing the appropriate presentation. to help solve problems, choose an effective solution method in solving a problem and find a solution to the given problem. These findings indicate the need for further research on learning styles.